PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PT. PLN (PERSERO) UNIT INDUK PUSAT PENGATUR BEBAN JAWA, MADURA, DAN BALI DIKANTOR UNIT PELAKSANA PENGATUR BEBAN DKI JAKARTA DAN BANTEN - Saskia Alfiani Romadhoni; Agrasadya (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of motivation and work discipline on employee performance PT. PLN (Persero) Central Load Regulator Unit of Java, Madura, and Bali at the Office of the DKI Jakarta and Banten Load Regulator Implementation Unit, both partially and simultaneously. The method used is the Quantitative Associative method. The population in this study were employees at PT. PLN (Persero) Central Load Regulator Unit of Java, Madura, and Bali at the Office of the DKI Jakarta and Banten Load Regulator Implementation Unit. The sampling technique used was the saturated sample method with a sample of 71 respondents. The data analysis method used simple linear regression test, multiple linear regression, correlation coefficient, determination coefficient, partial t test and F test. The results of this study indicate that there is an effect of motivation on employee performance at PT. PLN (Persero) UP2B DKI Jakarta and Banten, this can be proven from the simple linear regression equation Y = 4.868 + 0.869X1. The correlation value is 0.801 (very strong). The determination coefficient value is 64.2%. The calculated t value is 11.125 > t table 1.994 with a significance of 0.000 < 0.05. There is an influence of work discipline on employee performance at PT. PLN (Persero) UP2B DKI Jakarta and Banten, this can be proven from the simple linear regression equation Y = 10.305 + 0.445X2. The correlation value is 0.702 (strong). The determination coefficient value is 49.3%. The calculated t value is 8.184 > t table 1.984 with a significance of 0.000 < 0.05. Simultaneously, there is an influence of motivation and work discipline on employee performance at PT. PLN (Persero) UP2B DKI Jakarta and Banten, this can be proven from the multiple linear regression equation Y = 0.550 + 0.647X1 + 0.203X2. The correlation value is 0.703 (strong). The determination coefficient value is 70.3%. The calculated F value is 80.378 > Ftable 3.98 with a significance level of 0.000 < 0.05.